ARTS SUPPORTING ENGLISH LEARNING: HOW IT MAY HELP? - Anisa Putri Cahyani; Nuning Wahyu Astuti (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2022)
Incorporating arts in pedagogy has been studied and reported to be able to support students’ achievement; however, the studies of integrating arts in the English language learning especially in higher education in Indonesia remain low. This paper focuses on the recent literature review of arts integration within English language learning and how it has been implemented globally. The articles are then analyzed based on the forms of arts, the implementation, and the learners’ responses. Lastly, by reflecting the review results to Indonesian settings, the researcher reveals opportunities and ideas of integrating arts within English teaching learning in Indonesia that may have been neglected before.